CONCEPTION OF HIGHWAY QUALITY MANAGEMENT - I. I. Leonovich; E. V. Kashevskaya (Наука и техника)
The paper contains fundamental provisions pertaining to conception of highway quality control and formulated problems that are necessary to solve in order to ensure system management at three levels, namely: strategic, tactical and operative.